THE FDI-GROWTH NEXUS IN SOUTH AFRICA: A RE-EXAMINATION USING QUANTILE REGRESSION APPROACH - KHOBAI, Hlalefang; HAMMAN, Nicolene; MKHOMBO, Thando; MHAKA, Simba; MAVIKELA, Nomahlubi; PHIRI, Andrew (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
This study sought to contribute to the growing empirical literature by investigating the effects of FDI on per capita GDP growth for South Africa using time series data collected between 1970 and 2016. Compared to the majority of previous studies, we use quantile regressions which investigates the effects of FDI on economic growth at different distributional quantiles. Puzzling enough, the empirical results show that FDI has a negative influence on welfare at extremely low quantiles whereas at other levels this effect turns insignificant. Contrary, the effects of domestic investment on welfare is positive and significant at all levels. Collectively, these results have important implications for policymakers in South Africa. JEL Classification: C21, C31, E22, F43, O40.